Pengaruh Kegiatan Extra Feeding dan Pola Asuh Orangtua Terhadap Kemandirian Anak - Dine Trio Ratnasari; Nopiana Nopiana; Rizky Drupadi (JURNAL INOVATIF ILMU PENDIDIKAN, 2019)
The purpose of this study is to comprehensively understand the effect of extra feeding activities and parenting on children's independence. The method used in this study is an experimental method with children's independence as the main problem which is the dependent variable. In this study the sampling technique that will be used is multistage cluster sampling. The sample in this study was in two elementary schools namely SDN 4 Banjar Agung and SDN 5 Banjar Agung, researchers only chose students based on the results of questionnaires parenting parents based on authoritarian, permissive, democratic parenting categories and 10 students each so that the sample in this study was 30 students as a control class at SDN 4 Banjar Agung and 30 students as experimental classes at SDN 5 Banjar Agung. This research is an experimental design with 2x3 factorial design. Therefore, data analysis used a two-way ANOVA, if differences were tested, followed by the Tukey test or Scheffe test to determine which one was higher. From the findings, it can be recommended to use extra feeding activities with fun cooking to increase children's independence.Keywords: extra feeding activities, parenting, and independence children DOI: http://dx.doi.org/10.23960/jiip.v1i2.19171